2008
DOI: 10.1089/thy.2007.0124
|View full text |Cite
|
Sign up to set email alerts
|

Is It Meaningful to Preserve a Palsied Recurrent Laryngeal Nerve?

Abstract: Even on a palsied RLN, a positive electrophysiological response may still be yielded by intraoperative neuromonitoring. This means that there may retain residual innervations in laryngeal muscles. To prevent atrophy of a paralyzed vocal cord, further injury to a palsied RLN should be avoided. Even the palsied nerve should be saved whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Patients with RLN palsy in benign thyroid disease can experience recovery of the palsy and this has been previously documented [16]. In two of our patients, the RLN palsy fully recovered following surgery.…”
Section: Discussionsupporting
confidence: 76%
“…Patients with RLN palsy in benign thyroid disease can experience recovery of the palsy and this has been previously documented [16]. In two of our patients, the RLN palsy fully recovered following surgery.…”
Section: Discussionsupporting
confidence: 76%
“…For this reason, the IONM can be used to detect the correct position of the RLN (before visual confirmation early at the beginning of the procedure), stimulating via the probe the overlying tissue of the tracheo-esophageal groove as described by our technique. Recent consensus guidelines have recommended more extended surgery for differentiated thyroid cancers (DTC) and benign thyroid disease, i.e., total thyroidectomies [19][20][21][22][23]. Bilimoria demonstrated that total thyroidectomy results in lower recurrence rates and improved survival for differentiated thyroid cancer compared with less extensive procedures [20].…”
Section: Discussionmentioning
confidence: 99%
“…In thyroid cancer patient, preoperative laryngeal paresis usually results in sacrificing or reconstructing the RLN during thyroidectomy [23]. Some authors recently justified the preservation of the RLN using IONM despite local invasion of the nerve by extrathyroidal extension or regional lymph node metastases [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations